2023
DOI: 10.3390/polym15102284
|View full text |Cite
|
Sign up to set email alerts
|

Tough Structural Adhesives with Ultra-Resistance to Both High and Cryogenic Temperature

Abstract: Structural adhesion at high temperature has been a challenge for organic adhesives, and the commercially available adhesives that can work at a temperature above 150 °C is rather limited. Herein, two novel polymers were designed and synthesized via facile strategy, which involves polymerization between melamine (M) and M–Xylylenediamine (X), as well as copolymerization of MX and urea (U). With well-balanced rigid-flexible structures, the obtained MX and MXU resins were proved to be outstanding structural adhes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
2
1
Order By: Relevance
“…Therefore, the debonding energy increases from 5.34 ± 3.21 kN/m (HTA 0 ) to 61.16 ± 10.69 kN/m (HTA 0.5 ), 46.47 ± 7.22 kN/m (HTA 1 ), and 61.91 ± 20.12 kN/m (HTA 2 ), respectively, with an increase of 1045%, 770% and 1059%, respectively (Figure c). To the best of the authors’ knowledge, the lap-shear strength and the debonding work are 5 times higher than those reported in literatures , (Figure d), which is due to the relatively lower cross-sectional point of HTA 0.5 in the rheological modulus plot compared to HTA 1 . Taking HTA 0.5 as an example, it was further investigated at various temperatures and bonded to different substrates.…”
Section: Experimental Sectioncontrasting
confidence: 54%
“…Therefore, the debonding energy increases from 5.34 ± 3.21 kN/m (HTA 0 ) to 61.16 ± 10.69 kN/m (HTA 0.5 ), 46.47 ± 7.22 kN/m (HTA 1 ), and 61.91 ± 20.12 kN/m (HTA 2 ), respectively, with an increase of 1045%, 770% and 1059%, respectively (Figure c). To the best of the authors’ knowledge, the lap-shear strength and the debonding work are 5 times higher than those reported in literatures , (Figure d), which is due to the relatively lower cross-sectional point of HTA 0.5 in the rheological modulus plot compared to HTA 1 . Taking HTA 0.5 as an example, it was further investigated at various temperatures and bonded to different substrates.…”
Section: Experimental Sectioncontrasting
confidence: 54%
“…Bio-based PSAs, especially vegetable-oils-based PSAs, have been considered to be a promising potential alternative to petroleum-based PSAs, which are mainly derived from acrylics, silicones, ethylene vinyl acetates, polyurethanes, polyisoprenes, polybutadienes, etc. [ 3 , 4 ]. Vegetable oils are mainly triglycerides in which glycerol is esterified with three saturated or unsaturated fatty acids.…”
Section: Introductionmentioning
confidence: 99%
“…Over several decades, extensive studies have confirmed that the creep and stress relaxation curves of a material during extended mechanical testing exhibit similar shapes at different time points throughout the physical aging process of polymers [5,6]. These curves can be transposed along the time axis under varying circumstances to construct a master curve at a specific time point, thereby accelerating the process of characterizing the mechanical properties of materials [5,6]. Through examining relaxation phenomena in molecular chain segments, it has been observed that mechanical relaxation can occur at both high temperatures over short periods and low temperatures over extended durations.…”
Section: Introductionmentioning
confidence: 99%